SIRT1 attenuates severe ischemic damage by preserving cerebral blood flow. Issue 3 (11th February 2015) - Hattori, Yorito; Okamoto, Yoko; Nagatsuka, Kazuyuki; Takahashi, Ryosuke; Kalaria, Rajesh N.; Kinoshita, Makoto; Ihara, Masafumi
Abstract : Silent information regulator 2 homolog 1 (SIRT1) is a protein deacetylase that has been reported to suppress neurodegenerative and cardiovascular pathologies in model organisms. We have recently reported that SIRT1 overexpression preserves cerebral blood flow (CBF) after bilateral common carotid artery stenosis (∼50% stenosis) by the deacetylation of endothelial nitric oxide synthase. This study was designed to determine whether cerebral SIRT1 expression would be effective in a more severe model of cerebral ischemia caused by bilateral common carotid artery occlusion (BCAO) in vivo . Sirt1 -overexpressing (Sirt1-Tg) mice ( n =13) and their wild-type littermates ( n =17) were subjected to BCAO for 10 min using microaneurysm clips. Temporal CBF changes were measured by laser speckle flowmetry before and 5, 10 min, and 2 h after BCAO. Histological evaluation of hippocampal changes was performed 7 days after BCAO. Histological findings were significantly less severe in Sirt1-Tg mice than in wild-type mice; wild-type mice showed strokes in the hippocampus, whereas Sirt1-Tg mice had minimal hippocampal damage 7 days after BCAO. Consistent with this observation, wild-type mice showed a severe reduction in CBF to ∼20–25% of the baseline level during BCAO, whereas Sirt1-Tg littermates showed significantly preserved CBF up to 45–50% of the baseline level. Our study provides evidence for the promising role of SIRT1 in protecting against cerebral global ischemia by preserving CBF and restoring the cerebrovascular reserve. Abstract : Supplemental Digital Content is available in the text.